Preparation and oxidation of aluminum powders with surface alumina replaced by iron coating. Issue 3 (3rd July 2022) - Ali, Rashid; Ali, Fahad; Zahoor, Aqib; Shahid, Rub Nawaz; Tariq, Naeem Ul Haq; Ali, Ghulam; Ullah, Saad; Shah, Attaullah; Awais, Hasan Bin
ABSTRACT: Aluminum powders are well known for excellent release of energy during oxidation upon heating. However, this release of energy becomes limited due to formation of dense oxide (Al2 O3 ) layer on powder surface. In this study, reactivity of aluminum particles was improved by replacing oxide layer with metallic shell of iron using electroless plating technique. Three different bath compositions were selected for deposition of iron on aluminum particles. The surface morphology of prepared Al/Fe core–shell composite powder was characterized by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDX). Further, iron content in the composite powder was measured quantitatively using helium gas pycnometer while elemental analysis was performed by X-ray diffraction (XRD). Finally, thermo-physical behavior of the composite powder was investigated using simultaneous thermogravimetry–differential scanning calorimetry (TG–DSC). The results showed that the synthesized Al/Fe core–shell composite powder exhibits higher energy release in comparison to the uncoated aluminum powder upon heating in air (up to 1180 °C). The powder with the densest iron coating released the highest energy.